1992
DOI: 10.1093/jmedent/29.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Gonotrophic Cycle and Survivorship of Anopheles albimanus (Diptera: Culicidae) in Southern Mexico

Abstract: The length of the gonotrophic cycle of Anopheles albimanus was estimated by 12 mark-release-recapture studies conducted in corrals in southern Mexico from 1987 to 1990. The initial set of three mark-release studies indicated that the gonotrophic cycle takes at least 4 d based on the day when gravid mosquitoes were first recaptured. However, in later experiments, mosquitoes recaptured seeking hosts at 48 h after release were in Sella's and Christophers' stages I and II, but parity rates had nearly doubled, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In Bellevue, mosquitoes would take two to three blood meals before transmitting. However it is thought that A. albimanus violate these assumption of gonotrophic concordance by taking multiple meals during a gonotrophic cycle [ 49 , 50 ] or exhibit two gonotrophic cycles; shorter for parous mosquitoes and longer for nulliparous mosquitoes [ 51 ]. The study in Bellevue suggested that nulliparous A. albimanus required a second blood-meal to achieve fully reproductive capacity [ 25 ], hence the difference in gonotrophic cycles between Bellevue and Dajabón.…”
Section: Resultsmentioning
confidence: 99%
“…In Bellevue, mosquitoes would take two to three blood meals before transmitting. However it is thought that A. albimanus violate these assumption of gonotrophic concordance by taking multiple meals during a gonotrophic cycle [ 49 , 50 ] or exhibit two gonotrophic cycles; shorter for parous mosquitoes and longer for nulliparous mosquitoes [ 51 ]. The study in Bellevue suggested that nulliparous A. albimanus required a second blood-meal to achieve fully reproductive capacity [ 25 ], hence the difference in gonotrophic cycles between Bellevue and Dajabón.…”
Section: Resultsmentioning
confidence: 99%
“…A second pregravid blood meal has been recorded in field studies of several other New World anophelines including An. albimanus [ 54 ] and An. vestitipennis [ 55 ] in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Small arthropods such as flies and mosquitoes may easily be carried by prevailing winds or storms (Carlquist, 1974). However, many vectors of Plasmodium suffer very high mortality after taking a blood meal and producing a clutch of eggs such that very few survive to take a second blood meal and transmit the parasite (Rodriguez et al ., 1992; Fialho & Schall, 1995). The combined probability for the survival of an infected vector that is blown from one island to another must then be extremely small.…”
Section: Discussionmentioning
confidence: 99%